First-in-Man Clinical Experience Using a High-Definition 3-Dimensional Exoscope System for Microneurosurgery. Issue 6 (26th November 2018) - Khalessi, Alexander A; Rahme, Ralph; Rennert, Robert C; Borgas, Pia; Steinberg, Jeffrey A; White, Timothy G; Santiago-Dieppa, David R; Boockvar, John A; Hatefi, Dustin; Pannell, J Scott; Levy, Michael; Langer, David J
ABSTRACT: BACKGROUND: During its development and preclinical assessment, a novel, 3-dimensional (3D), high-definition (4K-HD) exoscope system was formerly shown to provide an immersive surgical experience, while maintaining a portable, low-profile design. OBJECTIVE: To assess the clinical applicability of this 3D 4K-HD exoscope via first-in-man surgical use. METHODS: The operative workflow, functionality, and visual haptics of the 3D 4K-HD exoscope were assessed in a variety of microneurosurgical cases at 2 US centers. RESULTS: Nineteen microneurosurgical procedures in 18 patients were performed exclusively using the 3D 4K-HD exoscope. Pathologies treated included 4 aneurysms, 3 cavernous malformations (1 with intraoperative electrocorticography), 2 arteriovenous malformations, 1 foramen magnum meningioma, 1 convexity meningioma, 1 glioma, 1 occipital cyst, 1 chiari malformation, 1 carotid endarterectomy, 1 subdural hematoma, 1 anterior cervical discectomy and fusion, and 2 lumbar laminectomies. All patients experienced good surgical and clinical outcomes. Similar to preclinical assessments, the 3D 4K-HD exoscope provided an immersive 3D surgical experience for the primary surgeon, assistants, and trainees. The small exoscope frame, large depth of field, and hand/foot pedal controls improved exoscope mobility, decreased need to re-focus, and provided unobstructed operative corridors. Flexible positioning of the camera allows the surgeon's posture to be kept in a neutral position with uncompromised viewing angles. CONCLUSION: The first-in-man clinical experience with the 3D 4K-HD exoscope confirms its excellent optics and ergonomics for the entire operative team, with high workflow adaptability for a variety of microneurosurgical cases. Expanded clinical use of the 3D 4K-HD exoscope is justified.